2020
DOI: 10.1111/bjh.17173
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic herpes simplex virus type 1 (HSV‐1) in combination with lenalidomide for plasma cell neoplasms

Abstract: Oncolytic viruses exert an anti-tumour effect through two mechanisms: direct oncolytic and indirect immune-mediated mechanisms. Although oncolytic herpes simplex virus type 1 (HSV-1) has been approved for melanoma treatment and is being examined for its applicability to a broad spectrum of malignancies, it is not known whether it has an anti-myeloma effect. In the present study, we show that the third-generation oncolytic HSV-1, T-01, had a direct oncolytic effect on five of six human myeloma cell lines in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Furthermore, it has been recently reported that oncolytic HSV-1, T-01, induces direct oncolysis and immune activation governed by plasmacytoid dendritic cells (pDCs) and natural killer (NK) cells in plasma cell neoplasms. 11 Additionally, oHSV-1 also induced apoptosis in primary MM cells. It was observed to be higher in the total cellular fraction isolated from BM aspirates of patients with MM, compared to that isolated from PB, and also in the BM CD138 + cellular fraction compared to the BM CD138 À cellular fraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been recently reported that oncolytic HSV-1, T-01, induces direct oncolysis and immune activation governed by plasmacytoid dendritic cells (pDCs) and natural killer (NK) cells in plasma cell neoplasms. 11 Additionally, oHSV-1 also induced apoptosis in primary MM cells. It was observed to be higher in the total cellular fraction isolated from BM aspirates of patients with MM, compared to that isolated from PB, and also in the BM CD138 + cellular fraction compared to the BM CD138 À cellular fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been recently reported that oncolytic HSV-1, T-01, induces direct oncolysis and immune activation governed by plasmacytoid dendritic cells (pDCs) and natural killer (NK) cells in plasma cell neoplasms. 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subcutaneous xenograft myeloma model, HSV-1 treatment decreased tumour volume after intratumoral injection [ 42 ]. Another study reported similar findings in vitro and examined if the presence of an immune cell population would enhance the cytotoxic effect of HSV-1 [ 43 ]. Co-cultures of myeloma cell lines and PBMC cells (from healthy donors or myeloma patients) were treated with HSV-1.…”
Section: The Use Of Oncolytic Viruses In the Treatment Of Multiple Myelomamentioning
confidence: 94%
“…HSV-1 killed various lineages of hematological tumor cells. 36,37 Notably, intratumoral injection of T-VEC into primary cutaneous B-cell lymphoma in a phase I trial induced 6 complete responses and 5 partial responses out of 13 patients in injected lesions. 38 Two out of 3 patients with non-injected lesions showed an abscopal effect on these lesions.…”
Section: Oncolytic Virusesmentioning
confidence: 99%